Consuming and producing linked open data: the case of OpenCourseWare. Issue 1 (28th January 2014) - Piedra, Nelson; Tovar, Edmundo; Colomo-Palacios, Ricardo; Lopez-Vargas, Jorge; Alexandra Chicaiza, Janneth
Abstract : Purpose: – The aim of this paper is to present an initiative to apply the principles of Linked Data to enhance the search and discovery of OpenCourseWare (OCW) contents created and shared by the universities. Design/methodology/approach: – This paper is a case study of how linked data technologies can be applied for the enhancement of open learning contents. Findings: – Results presented under the umbrella of OCW-Universia consortium, as the integration and access to content from different repositories OCW and the development of a query method to access these data, reveal that linked data would offer a solution to filter and select semantically those open educational contents, and automatically are linked to the linked open data cloud. Originality/value: – The new OCW-Universia integration with linked data adds new features to the initial framework including improved query mechanisms and interoperability.